Anaesthetic management of a pregnant woman with uncorrected tetralogy of fallot for caesarean section - Badhan, Anjana; Chandel, Ankita; Adhikari, Shreya Das (International Journal of Research in Medical Sciences, 2019)
Tetralogy of fallot (TOF) is the most commonly encountered congenital cyanotic heart disease in pregnant females and maternal mortality approaches 10% in unrepaired TOF. General anesthesia is classically considered the technique of choice for incidental surgery in TOF and neuraxial anesthesia is considered relatively contraindicated. However, general anesthesia for caesarean section can increase maternal morbidity. Author report a case of caesarean section performed under epidural anesthesia in patient with uncorrected TOF.